2017
DOI: 10.18632/oncotarget.20340
|View full text |Cite
|
Sign up to set email alerts
|

LINC00461, a long non-coding RNA, is important for the proliferation and migration of glioma cells

Abstract: An increasing number of reports have revealed that long non-coding RNAs are important players in tumorigenesis. Here we showed that long non-coding RNA LINC00461 is highly expressed in glioma tissues compared to non-neoplastic brain tissues. The knockdown of LINC00461 suppressed cyclinD1/A/E expression which led to G0/G1 cell cycle arrest and inhibited cell proliferation in glioma cells. LINC00461 suppression also inhibited glioma cell migration and invasion. The function of LINC00461 in glioma cells is partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 60 publications
3
39
0
Order By: Relevance
“…LINC00707 overexpression promotes cell proliferation and migration in lung adenocarcinoma by regulating Cdc42 . LINC00461, a member of lncRNAs, is located at an intergenic region of the human chromosome 5 between two protein‐coding genes MEF2C and TMEM161B, respectively . LINC00461 has been reported to be one of the significantly up‐regulated lncRNAs in glioblastomas and metastatic prostate cancers .…”
Section: Discussionmentioning
confidence: 99%
“…LINC00707 overexpression promotes cell proliferation and migration in lung adenocarcinoma by regulating Cdc42 . LINC00461, a member of lncRNAs, is located at an intergenic region of the human chromosome 5 between two protein‐coding genes MEF2C and TMEM161B, respectively . LINC00461 has been reported to be one of the significantly up‐regulated lncRNAs in glioblastomas and metastatic prostate cancers .…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] LINC00461 is a novel cancer-related lncRNA, transcribed from a gene located at an intergenic region of human chromosome 5. 11 However, the role of LINC00461 in BC is still unclear. 11 However, the role of LINC00461 in BC is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Mounting studies have suggested the significant role of lncRNAs in the development of cancers, including NSCLC [14][15][16]. Herein, we selected LINC00461 for investigation because it has been demonstrated as an oncogene in multiple cancers, such as breast cancer, myeloma, and glioma [17][18][19]. In the present study, we firstly found that LINC00461 was up-regulated in NSCLC, and indicated poor prognosis.…”
Section: Discussionmentioning
confidence: 65%
“…The effect of lncRNAs on NSCLC has also been uncovered by mounting researches [14][15][16]. Long intergenic non-protein coding RNA 461 (LINC00461) demonstrated oncogenic performance in breast cancer, myeloma, and glioma [17][18][19], promoting cell growth, migration, and invasion, but it is not researched in NSCLC.…”
Section: Introductionmentioning
confidence: 99%